IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 001 BANTAYAN - Ernita Ernita; Zetra Hainul Putra; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to improve student learning outcomes with the implementation of cooperative learning model make a match type in the fourth graders of SDN 001 Bantayan. Subject in this research is 30 students that consist of 12 males and 18 females. Method used in this research is classroom action research (PTK) that consists of two cylces. This research conducts from March 25th to April 16th 2015. Data shows that learning process and social science learning outcomes increase. The average learning outcomes increases from 61,1 at based score into 71,6 in the first cycle, and 77 in the second cycles with 96.67% classical completeness. Students’ activities also increase from 54,1% with less category in the first meeting of first cycle into 95,8% with very good category in the second meeting of second cycle. It is similar to the teacher’s activities that increases from 58,3% with less category in the first meeting of first cycle. The increase of students’ learning outcomes is due to the increase of students’ and teacher’s activities. It can be concluded that the application of cooperative learning model make a match type can improve social science learning outcomes of grade IV SDN 001 Bantayan.Keywords: Social Science Learning Outcome, Cooperative Learning Model Make A Match